Microlearning Media for Language Literacy : A Learning Innovation for Elementary School Students - Nurhafit Kurniawan; Muhammad Agus Sugiarto; Arie Eko Cahyono (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to develop and test the effectiveness of microlearning-based instructional media in improving the language literacy skills of elementary school students. The microlearning media developed consists of short videos using a chunk-based approach that includes pre-learning, core, and post-learning activities. The study employed the research and development with ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The instruments used included surveys, interviews, and observations, while data analysis techniques involved quantitative analysis (pretest and posttest) and qualitative analysis from interviews and observations. Validation was carried out by media and education experts, followed by revisions based on the feedback provided. The implementation involved 60 fourth and fifth-grade students at elementary schools for Indonesian language lessons. Evaluation results showed an average increase of 34.35% in students' language literacy skills after using the media. Students also gave positive feedback on the clarity and presentation of the materials through the microlearning videos. Based on these results, microlearning media can be considered an effective tool for improving students' language literacy, reading skills, reading comprehension, writing skills, vocabulary mastery, and sentence construction.